Autonomous Mapping in Polluted Environments (Hungarian Journal of Industry and Chemistry, 2010)
The need of ecological robots is imposed by the nowadays trend towards protecting the environment and the human factor. New researches in this area have arisen in the past years. In the next few lines an overview of the state of the art in this domain will be made, proposals go from robots designed to repair power line damage to robots for capturing photos of animals in the wild without human intervention. The main objective in this paper is to demonstrate the autonomous navigation of a mobile robot in a polluted environment. So far the research on robots used for detection of gas sources was focused mainly on indoor environments, but, in the recent years, a constant move towards the outdoor environment can be observed. There can be found several researches with different applications in the area of ecological robots.
Keywords: autonomous mobile robots; mapping; navigation; polluted enviromnets